A season for tending - Woodsmall, Cindy (Colorado Springs, Colo. : Waterbrook Press, 2012)
Rhoda Byler's gift with plants leads to the enmity of a young man in her Old Order Amish community, but when she meets Samuel King, whose orchard is struggling, he suggests that they can solve each other's problems.
Keywords: Amish -- Fiction